Management Deep Health Literacy Increase Obedience Treatment of Patients Hypertension - Andi Satriana; Andi Bintang; Irfan Madamang; Magdalena Limbong (IJCS: International Journal of Community Service, 2022)
Hypertension, a non-communicable disease, is the leading cause of premature death worldwide. To control hypertension, self-management efforts and lifestyle changes are needed, such as managing diet, getting enough rest, exercising, and taking medication regularly (although hypertension cannot be cured, it can be controlled). Utilization of health literacy can increase the understanding and attitude of maintaining one's own health. This counseling aims to get an overview of efforts to control hypertension through the use of health literacy resources. This community service aims to get an overview of health literacy management in increasing medication adherence in hypertensive patients. The method of this community service is the method through counseling entitled "Management of Health Literacy in Increasing Compliance". Treatment of Hypertension ", amounting to 25 respondents. Results: show that there is an increase in compliance that can be obtained after carrying out community service regarding counseling on Health Literacy Management in Improving Patient Compliance Hypertension (92%) with Utilize health literacy resources obtained from health center staff. With this dedication, it is hoped that it can provide important information for hypertension sufferers regarding the importance of efforts to control hypertension by increase literacy health.